2016
DOI: 10.1038/srep19171
|View full text |Cite
|
Sign up to set email alerts
|

Support for the Microgenderome: Associations in a Human Clinical Population

Abstract: The ‘microgenderome’ provides a paradigm shift that highlights the role of sex differences in the host-microbiota interaction relevant for autoimmune and neuro-immune conditions. Analysis of cross-sectional self-report and faecal microbial data from 274 patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) suggests that commensal gut microorganisms may play both protective and deleterious roles in symptom expression. Results revealed significant sex-specific interactions between Firmicutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Our research 6 indicated support for the microgenderome by showing sex-specific associations between gut microbiota and symptom presentation in ME/CFS (detailed below). Results from faecal microbial assessments and self-reported symptoms were analyzed from 274 ME/CFS patients.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Our research 6 indicated support for the microgenderome by showing sex-specific associations between gut microbiota and symptom presentation in ME/CFS (detailed below). Results from faecal microbial assessments and self-reported symptoms were analyzed from 274 ME/CFS patients.…”
Section: Introductionsupporting
confidence: 63%
“…Twin studies have revealed that the once similar microbial composition of opposite-sex twins becomes distinctly different after puberty when compared to same-sex twins that remain compositionally similar 5 . Application of the microgenderome lens has only recently been applied to a human clinical population 6 . The focus of this addendum is to provide a comprehensive summary of the original results and additional commentary on our earlier findings.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In male subjects, the abundance and prevalence of Prevotellaceae , which was the sole strong determinant of a sample plot being located in the PC1-positive/PC2-positive direction in the PCA analysis, were both significantly higher ( P  < 0.01) than in female subjects (Table 4), which may account for the distinct partitioning between cluster 1 and cluster 2 in the male subjects. Recent studies have demonstrated that the composition of the gut microbiota is gender-specific (microgenderome) and that there is a gender-specific, bidirectional relationship between the host and the gut microbiota that is mediated via sex hormones [7, 29]. This suggests that the differences in the composition of the fecal microbiota observed between the female and male subjects in the present study are a result of a gender-specific relationship between the host and their gut microbiota.…”
Section: Discussionmentioning
confidence: 54%